Delayed Diagnosis of Foreign Bodies in Children's Tracheobronchial Trees: A Review Radio-Clinical Diagnosis and Treatment: 133 Cases- Tehran .......... IJMTFM (2011) 1(1): 24-29 - Agin, Kh (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Foreign body aspiration (FBA) of tracheobronchial trees is accidental evidence in children. It occurs the most common in less than 3-year age old. Diagnosis of inhaled FB is a dilemma in the pediatric, particularly in delayed or missed conditions. The aim of the study assessed the clinical features and rigid bronchoscopic finding of aspirated FB in tracheobronchial trees of children. Martial and Methods:Medical records of aspirated FB among children gathered based on the International cod system from 1987 to 2007 years. All patients who removed FB were entered into the study. Results: a total 133 cases enrolled in the study with mean age 3.51±2.55 (51 boys and 82girls). 85% of aspirated FB frequency detected under five years, with 78%peak incidence in four years oflife. Delayed duration of FB aspiration to the onset of removing was 90.62± 68.13 SD days. One hundred and six (79.7%) was detected vegetable’s FB on the tracheobronchial tract. History of aspirated FB did not find in 60% of cases. The most common clinical presentation was chronic cough and respiratory tract infections. Chest x-ray had positive signs in 79.7 %( 106) of the subjects. Conclusion: chronic cough or recurrent lower respiratory tract infection should be particularly suggested missed FB in the airways of children under the age four years. Detection of organic FB was difficult within airways. In addition, chest x-ray and well-inform history can be benefited in the early diagnosis. Giving information about aerated FB to the parents may be decreased length of delayed time to the onset of diagnosis. Moreover, the parents should not be worried from evaluation of children's airways by bronchoscopy.